2021
DOI: 10.1038/s41598-021-84769-7
|View full text |Cite
|
Sign up to set email alerts
|

Cyproterone acetate acts as a disruptor of the aryl hydrocarbon receptor

Abstract: Prostate cancer is a major cause of death in males. Cyproterone acetate (CPA), the steroidal anti-androgen for part of androgen deprivation therapy, may block the androgen-receptor interaction and then reduce serum testosterone through its weak anti-gonadotropic action. In addition to CPA inducing hepatitis, CPA is known to cause liver tumors in rats also. Aryl hydrocarbon receptor (AhR) is a cytoplasmic receptor and regulates multiple physiological functions. CYP1A1 is an AhR-targeted gene. We found that CPA … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 46 publications
(50 reference statements)
0
2
0
Order By: Relevance
“…However, the related results are controversial. In vitro studies have shown that the antiandrogens cyproterone acetate and flutamide have inhibitory effects on androgen-induced HCC cell growth ( Koch et al, 2015 ; Chen et al, 2021 ). In contrast, large clinical trials with leuprolide and flutamide (antiandrogens) have failed to improve patient survival ( GdEedTdC, 2004 ).…”
Section: Discussionmentioning
confidence: 99%
“…However, the related results are controversial. In vitro studies have shown that the antiandrogens cyproterone acetate and flutamide have inhibitory effects on androgen-induced HCC cell growth ( Koch et al, 2015 ; Chen et al, 2021 ). In contrast, large clinical trials with leuprolide and flutamide (antiandrogens) have failed to improve patient survival ( GdEedTdC, 2004 ).…”
Section: Discussionmentioning
confidence: 99%
“…Ethynyl estradiol (a synthetic estrogen used as contraceptive drug) caused liver effects (congestion, focal areas of hemorrhage, vacuolation of cytoplasm, distended sinusoids with dilated central veins) in female rats and the extent and severity of the damage depends on the dose and the time of administration [23]. More recently, CPA demonstrated also to be an aryl hydrocarbon receptor (AhR) agonist in mouse and an AhR antagonist in human cells [24]. Indeed, in both male and female C57BL/10J mice, long-term exposure to 800 ppm of CPA in the diet induced hepatocyte hypertrophy and increased fat and glycogen [25].…”
Section: Discussionmentioning
confidence: 99%